Factors Influencing the Effectiveness of Village Fund Allocation (ADD) Management in Tanjung Raja Village, Tanjung Raja Sub-district, North Lampung District - Susanto, Heri; Darmawan, Jaka (Proceeding International Conference on Information Technology and Business, 2023)
This research aims to determine the influence of the effectiveness of village fund allocation management in Tanjung Raja Village, Tanjung Raja Sub-district, focusing on planning, implementation, accountability, and accountability of the village fund allocation. This quantitative research utilized primary data sources and a non-probability sampling method. Data were collected through questionnaires and interviews with village government officials involved in fund management. Data analysis employed effectiveness techniques and ratio criteria. The results indicate that the effectiveness of village fund allocation management falls within the effective category.Keywords: Village fund allocation, Effectiveness, Management